Discitis after spinal anaesthesia in lower limb surgery in orthopaedics - Chaudhary, P; Shrestha, B P; Khanal, G P; Maharjan, R; Rijal, R; Paneru, S R; Yadav, D K (Health Renaissance, 2012)
Spinal Anaesthesia has its own complications from beginning of its use but due to lower incidence of its complications, its popularity has continued to increase worldwide. We present a case of 51 year old gentleman who had undergone removal of implant (plate from tibia and Rush nail from femur) at Orthopaedic Department of B.P.Koirala Institute of Health Sciences, Dharan, Nepal with complain of low back pain with radiation to right lower limb, decreased sensation, difficulty in voiding following a surgery. We report this case for its rarity and unique characteristics and to highlight the importance of bits timely treatment so that serious neurological complications do not occur. DOI: http://dx.doi.org/10.3126/hren.v10i2.6587 Health Renaissance 2012; Vol 10 (No.2); 150-152